Polymerase Chain Reaction on Respiratory Tract Specimens of Immunocompromised Patients to Diagnose Pneumocystis Pneumonia: A Systematic Review and Meta-analysis - Brown, Lottie; Rautemaa-Richardson, Riina; Mengoli, Carlo; Alanio, Alexandre; Barnes, Rosemary A; Bretagne, Stéphane; Chen, Sharon C A; Cordonnier, Catherine; Donnelly, J Peter; Heinz, Werner J; Jones, Brian; Klingspor, Lena; et al. (Clinical Infectious Diseases: An Official Publication of the Infectious Diseases Society of America, 2024)
This meta-analysis demonstrated very high diagnostic performance of PCR assays when used as screening tests for Pneumocystis pneumonia in high-risk patient groups, regardless of HIV status. qPCR on bronchoalveolar lavage fluid samples provided optimal sensitivity, closely followed by qPCR on induced sputum, while also providing adequate specificity., Graphical abstractThis graphical abstract is also available at Tidbit: https://tidbitapp.io/tidbits/pcr-on-respiratory-tract-specimens-of-immunocompromised-patients-to-diagnose-pneumocystosis-pcp-a-systematic-review-and-meta-analysis-89aa7a50-efbc-4ebb-8f20-c17d207e8d8e?utm_campaign=tidbitlinkshare&utm_source=ITP

Global guideline for the diagnosis and management of rare mould infections: an initiative of the European Confederation of Medical Mycology in cooperation with the International Society for Human and Animal Mycology and the American Society for Microbiology - Hoenigl, Martin; Salmanton-García, Jon; Walsh, Thomas J; Nucci, Marcio; Neoh, Chin Fen; Jenks, Jeffrey D; Lackner, Michaela; Sprute, Rosanne; Al-Hatmi, Abdullah M S; Bassetti, Matteo; Carlesse, Fabianne; Freiberger, Tomas; et al. (The Lancet Infectious Diseases, 2021)